2019
DOI: 10.3390/ijms20020436
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Hypoxia-Inducible Factor 1α (HIF-1α) and Genes of Related Pathways in Altered Gravity

Abstract: Immune system deterioration in space represents a major risk, which has to be mitigated for exploration-class missions into the solar system. Altered gravitational forces have been shown to regulate adaptation processes in cells of the immune system, which are important for appropriate risk management, monitoring and development of countermeasures. T lymphocytes and cells of the monocyte-macrophage system are highly migratory cell types that frequently encounter a wide range of oxygen tensions in human tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 87 publications
3
33
0
1
Order By: Relevance
“…The expression of osteogenic markers such as Runx2 and OCN were also decreased and these results confirmed that dexamethasone could repress the ability and function of osteoblasts. Recent reports have shown that HIF-1α could regulate PDK1 to mediate metabolic effects in different types of cells (15,27). Therefore, we examined PDK1 expression by western blotting.…”
Section: Downregulation Of Hif-1α and Pdk1 By Dexamethasonementioning
confidence: 98%
“…The expression of osteogenic markers such as Runx2 and OCN were also decreased and these results confirmed that dexamethasone could repress the ability and function of osteoblasts. Recent reports have shown that HIF-1α could regulate PDK1 to mediate metabolic effects in different types of cells (15,27). Therefore, we examined PDK1 expression by western blotting.…”
Section: Downregulation Of Hif-1α and Pdk1 By Dexamethasonementioning
confidence: 98%
“…The TEXUS-51 mission procedures have been previously described [13,14,55,56]. Briefly, three syringes were assembled into one unit.…”
Section: Texus-51 Mission Proceduresmentioning
confidence: 99%
“…Human Jurkat T cell culture was performed as previously described [13,14,55,56] in the ESRANGE Space Center laboratory facilities. Briefly, sterile plastic syringes were filled with 0.5 mL Jurkat cells (25 million cells).…”
Section: Experimental Preparation Procedures For Texus-51 Experimentsmentioning
confidence: 99%
See 2 more Smart Citations